Optimalisasi Hasil Belajar Peserta Didik Mata Pelajaran IPS (Ilmu Pengetahuan Sosial) KD. 3.3.5/4.3.5 Materi Ekonomi Kreatif melalui Model Project Based Learning Metode Diskusi Kelompok di Kelas IX.6 MTsN 1 Kota Payakumbuh Semester Genap T.P 2021/2022 - Sri Mulyani (Journal on Education, 2022)
This research is motivated by the low learning outcomes of Social Sciences (IPS) students in class IX.6 MTsN 1 Payakumbuh City. Besides, the lack of activeness and interest of students in the learning process. The purpose of this study was to find out whether the project based learning model and group discussion methods could improve the Social Sciences (IPS) learning outcomes of class IX.6 MTsN 1 Payakumbuh City students in the even semester of 2021/2022. This research method is Classroom Action Research. The research population is class IX.6 students, researchers and collaborators. This research took place from January to March 2022. The results showed that the Project Based Learning Model group discussion method could improve social studies learning outcomes for students in class IX.6 MTsN 1 Payakumbuh City. The average learning outcomes and the percentage of pre-cycle knowledge completeness achieved by the participants got an average score of 66 and the percentage of completeness was 50%. There was an increase in the first cycle the average value rose to 75 and the percentage of completeness to 73% and increased again in the second cycle the average value became 87 and the percentage of completeness reached 95%. Meanwhile, the average value of pre-cycle skills is 68 and the percentage of pre-cycle completeness is 63%. For the average value in the first cycle rose to 74 and the percentage of completeness also increased to 73%. Meanwhile, in the second cycle, the average value increased to 86 and the percentage of completeness reached 98%. The conclusion obtained from this study is that the application of the Project Based Learning model and group discussion methods can improve learning outcomes in Social Sciences (IPS) in class IX.6 MTsN 1 Payakumbuh City even semester 2021/2022.